Redesain Meja Workshop Kayu untuk Praktik Mahasiswa Desain Produk Industri dengan Pendekatan SCAMPER - R Moch Rizal Hafiyan; Handayani Madania Insani; Ghia Tri Jayanti (Besaung : Jurnal Seni Desain dan Budaya, 2026)
In wood-based practical learning, Industrial Product Design students require facilities that support efficiency, ergonomics, and workplace safety. Currently used  router woodworking benches suffer from limitations in stability, load capacity, and work surface dimensions that do not align with user anthropometry. This study aims to redesign a portable wood  workshop table using the SCAMPER method, focusing on functional enhancement, ergonomic adaptation, and alignment with beginner students’ needs. A Human-Centered Design framework was employed, supported by student anthropometric data for dimensional adjustments. The redesign features an expanded work surface improved structural stability via aluminum frame with cross-bracing, a modular system for combining two tables, and ergonomic component reorganization based on primary, secondary, and tertiary work zones. The final design demonstrates significant potential in enhancing workflow efficiency, postural comfort, and usage flexibility within educational  workshop settings